Effects of Nicotine and Depressive Traits on Affective Priming of Lateralized Emotional Word Identification - Gilbert, David G. (2008)
Based on evidence suggesting that depressive traits, emotional information processing, and the effects of nicotine may be mediated by lateralized brain mechanisms, analyses assessed the influence of depressive traits and nicotine patch on emotional priming of lateralized emotional word identification in 61 habitual smokers. Consistent with hypotheses, nicotine as compared to placebo patch enhanced right visual field (RVF) emotional word identification while decreasing performance of emotional word identification in the left visual field (LVF). Nicotine also enhanced positive affect and decreased negative affect. Consistent with the Heller model of depression, scoring high in depressive traits was associated with a general decrease in LVF emotional word identification. Additionally, this general LVF deficit was especially pronounced for positive word identification in individuals scoring high in trait depression. Positive primes facilitated positive target identification in the RVF and negative primes facilitated negative target identification in the LVF. Thus, nicotine promoted a LVF word-identification deficit similar to that observed in those with depressive traits. However, nicotine also enhanced RVF processing and reduced negative affect, while it enhanced positive affect.